Interpreter Training in Spain: Past and Present - Martin, Anne (MonTi Monografías de Traducción e Interpretación, 2016)
This paper deals with interpreter training in Spanish universities since its onset in 1979. Problems associated with the interpreting component in the recently phased out Licenciatura (4 year undergraduate course) in Translation and Interpreting are analysed. Such problems included the presence of compulsory subjects in the main conference interpreting techniques, without other prerequisites for beginning this training being guaranteed. At the current time a new degree is being introduced in the framework of the EHEA (Grado, also a 4 year undergraduate course) which affords much more freedom to the universities in the design of their syllabus. The results are very varied. Many universities have reduced their compulsory credits in interpreting and now offer more optional credits. Despite this trend, there are still a significant number of universities with compulsory credits in simultaneous interpreting. Master’s Degrees seem to be having difficulties in becoming consolidated and new genres of interpretation (other than conference interpreting) are being included in degree programmes.